Polymorphism of Angiotensin I Converting Enzyme Becomes an Innate Property in Renal Failure - MANIKANDAN.T; INAMUL HASAN MADAR; PRIYADARSHAN.K; SHYAM K.P; ANIL KUMAR (International Journal of Pharma and Bio Sciences, 2010)
Renal failure or kidney failure is a situation in which the kidneys fail to function adequately. Angiotensin converting enzyme plays a pivotal role in blood pressure regulation and electrolyte balance by hydrolyzing angiotensin I to angiotensin II. The Angiotensin Converting Enzyme (ACE) gene contains a polymorphism which is believed to be associated with the interpersonal variability of ACE levels in circulating blood. Elevated angiotensin II level makes deleterious effects on renal hemodynamics and induces the expression of other growth factors, leading to glomerulosclerosis. This paper attempts to find the association of ACE polymorphism with renal failure using Random Amplification of Polymorphic DNA technique arriving to the major conclusion that ACE polymorphism is an innate property in End Stage Renal Failure (ESRF) and ACE screening would be a valuable diagnostic tool in screening clinical ESRF.